2018
DOI: 10.1016/j.ophtha.2017.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mortality with Ocular Diseases and Visual Impairment in the Age-Related Eye Disease Study 2

Abstract: In AREDS2, the presence of late AMD, bilateral cataract surgery, and VA less than 20/40 was associated with decreased survival. However, oral supplementation with omega-3 fatty acids, lutein plus zeaxanthin, zinc, or beta-carotene had no statistically significant impact on mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…Our association between late AMD and mortality not specific to CVD or cancer is in agreement with several previous studies, 15 , 45 but not others. 12 The reasons underlying the association of AMD with increased risk of mortality not due to CVD or cancer are still unclear.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our association between late AMD and mortality not specific to CVD or cancer is in agreement with several previous studies, 15 , 45 but not others. 12 The reasons underlying the association of AMD with increased risk of mortality not due to CVD or cancer are still unclear.…”
Section: Discussionsupporting
confidence: 94%
“…The findings from previous population-based studies 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 40 , 41 on associations between AMD and mortality are summarized in eTable 4 in the Supplement . Our finding that the presence of late AMD was associated with an increased risk of all-cause mortality is in line with the Age-Related Eye Disease Study (AREDS), 14 AREDS2, 15 and Beaver Dam Eye Study. 16 , 20 Other population-based studies 12 , 13 , 17 , 18 , 19 have reported significant associations between any and mild AMD and all-cause mortality in subpopulations only.…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐VEGFA therapy in wet AMD is considered to be safe for patients, even although some side‐effects have been reported . Moreover, Papudesu et al showed that AREDS2 participants with wet AMD in one eye at baseline had a statistically significant increased risk for mortality compared with patients having no or only a few drusen . Moreover, a visual acuity less than 20/40 was associated with a reduced survival.…”
Section: Discussionmentioning
confidence: 99%
“…12,57 Moreover, Papudesu et al showed that AREDS2 participants with wet AMD in one eye at baseline had a statistically significant increased risk for mortality compared with patients having no or only a few drusen. 58 between advanced AMD and mortality. 60 Hanhart et al noted an increased mortality in wet AMD patients after myocardial infarction (MI) treated with bevacizumab as compared to non-treated individuals.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we used the term "percentage of death" instead of "mortality rate". Second, the presenting visual acuity or the presence of neovascular age-related macular degeneration, which are reported to have relatively superior predictive value for mortality, could not be used in this study because of limitations in the disability registration data regarding visual function 15,21,39 . Additionally, individuals with treatable transient blindness conditions, especially those caused by severe cataracts, could not be included in the blindness group in this study, in contrast with previous papers 15,18,31,40 .…”
Section: Discussionmentioning
confidence: 99%